Assessment of suspected adverse drug reactions in elderly patients with diabetes mellitus based on a Portuguese spontaneous reporting database: analysis of reporting from 2008 to 2018. Issue 7 (3rd July 2021) - Monteiro, Cristina; Silvestre, Samuel; Duarte, Ana Paula; Alves, Gilberto
ABSTRACT: Background: Age is one of the most important risk factors in the development of diabetes mellitus and certain drug classes indicated for this condition may be associated with clinically important adverse drug reactions (ADRs). The aim of this study was to analyze the suspected ADRs in older patients with diabetes mellitus, reported to the Portuguese Pharmacovigilance System from 2008 to 2018. Research design and methods: A retrospective analysis of suspected ADRs reports was performed, involving patients aged ≥65 years. Results: Of a total of 751 reports collected, 439 were considered serious, 199 led to hospitalization and in 19 of them occurred a fatal outcome. Most of them were observed in females (n = 393) and involved patients belonging mainly to the age group 65–74 years (n = 405). Taking into account a total of 2134 suspected ADRs, the most frequent were hypoglycemia (2.67%) and lactic acidosis (2.62%). The drugs specifically indicated for glycemic control were the most frequently involved in ADRs. Conclusions: Most of the ADRs were reported as serious and were mainly associated to drugs in diabetes mellitus. In addition, the majority of them, such as hypoglycemia, are preventable, highlighting the importance to identify possible factors that determine this occurrence, especially in the elderly.